Pengembangan Media Pembelajaran Kimia Berbasis Augmented Reality Pada Materi Senyawa Karbon - Sahidi, Samsul; Jeckson Siahaan; Supriadi, Supriadi (Chemistry Education Practice, 2025)
This study aims to determine the feasibility and practicality of interactive learning media based on augmented reality for carbon compounds. This research is a type of development research that adopts the 4D model (define, design, develop, disseminate) but is limited only to the development stage (develop). The population in this study consisted of 124 students from SMAN 1 Labuhan Haji. The sampling technique used in this study was random sampling. The assessment aspects evaluated by three validators have three aspects measured through expert validation sheets. The level of practicality of the media was measured through a practicality questionnaire sheet completed by 24 students of Class XI MIPA at SMAN 1 Labuhan Haji. The results showed that the level of media feasibility, as assessed by the validator, was 0.68, indicating that the developed media had a high level of validity. The results of the media practicality test showed that students gave positive responses to all media components, with a practicality percentage of 87.5%. Based on these results, it can be concluded that the media developed is feasible and practical to use.